Aplicação de polímeros sustentáveis na indústria de máquinas e implementos agrícolas - Maiorka, Jaqueline Varela (2014)
n the machinery industry and agricultural implements one of the most widespread polymer is high density polyethylene (HDPE). On the other hand, companies in this sector are increasingly seeking to rely on the concept of sustainable development, which includes the dimensions of environmental sustainability, economic and social. The virgin high density polyethylene (HDPE-V) has a high cost, when compared to other similar polymers. This fact together with the high waste during processing, attend to a major concern of this research, is the recycling and reprocessing of this raw material, maintaining the quality standards required for the manufacture of components of agricultural machinery and implements. Thus, we seek to partial substitution of virgin high density polyethylene (HDPE-V) by high green density polyethylene (HDPE-Ve), as well as the partial substitution by recycled high density polyethylene (HDPE-R). However, this replacement must be done safely, in care of appropriate quality questions for the components of agricultural machinery and implements. Were selected twelve different compositions of polyethylene and performed tensile tests, thermal tests DSC and TGA. We chose a computer simulation of a component project to evaluate the effect of using the various blends studied as specimens. The main objective of this simulation is a systematic point where the results may enable the design of components considering the use of different blends evaluated. The parts produced were subjected to inspection dimensional quality, roughness measurement and evaluation of homogeneity. The results of the tensile tests and thermal tests DSC and TGA showed that the HDPE-Ve presented values very close to those obtained for the HDPE-V. Results for HDPE-R showed deterioration of properties. The computer simulation followed by experimental production quality control parts proved to be a viable method for the safe use of HDPE HDPE-Ve-R under the conditions adopted in this work.